Oxidative stress and epigenetic mortality risk score: associations with all-cause mortality among elderly people - Gao, Xu; Gao, Xin; Schöttker, Ben; Brenner, Hermann (European journal of epidemiology, 2019)
Oxidative stress (OS) has been found to be related to accelerated aging and many aging-related health outcomes. Recently, an epigenetic “mortality risk score” (MS) based on whole blood DNA methylation at 10 mortality-related CpG sites has been demonstrated to be associated with all-cause mortality. This study aimed to address the association between OS and MS, and to assess and compare their performance in the prediction of all-cause mortality. For 1448 participants aged 50-75 of the German ESTHER cohort study, the MS was derived from the DNA methylation profiles measured by Illumina HumanMethylation450K Beadchip and the levels of two urinary OS markers, 8-isoprostane (8-iso) and oxidized guanine/guanosine [including 8-hydroxy-2′-deoxyguanosine (8-oxo)], were measured by ELISA kits. Associations between OS markers and the MS were evaluated by linear and ordinal logistic regression models, and their associations with all-cause mortality were examined by Cox regression models. Both OS markers were associated with the MS at baseline. The 8-iso levels and MS, but not 8-oxo levels, were associated with all-cause mortality during a median follow-up of 15.1 years. Fully-adjusted hazard ratios (95% CI) were 1.56 (1.13-2.16) for the 4th quartile of 8-iso levels compared with the 1st, 1.71 (1.27-2.29) and 2.92 (2.03-4.18) for the moderate and high MS defined by 2-5 and > 5 CpG sites with aberrant methylation compared with a MS of 0-1, respectively. After controlling for 8-iso levels, the hazard ratios of MS remained essentially unchanged while the association of 8-iso levels with mortality was attenuated. This study demonstrates that OS is highly associated with the epigenetic MS, and the latter at the same time has a higher predictive value for all-cause mortality.
Gesehen am 15.05.2019